2011
DOI: 10.1111/j.1751-0813.2011.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of Coxiella burnetii infection in beef cattle in Queensland

Abstract: Background  Queensland has the highest incidence of Q fever in Australia. The aim of this study was to undertake a cross‐sectional seroprevalence survey of Coxiella burnetii, the causative agent of Q fever, in beef cattle in Queensland. Methods  Serum samples were tested by ELISA for both phase II and phase I antigens of the organism using an Australian isolate. Blood samples were collected at an abattoir that processes beef cattle originating from northern and north‐western Queensland, in addition to blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
1
21
1
2
Order By: Relevance
“…The risk of contacting Q fever in a rural setting has been extensively reported, and the direct correlation between animal handlers contracting Q fever from large ruminants has been previously identified (Stoker and Marmion, ; Lang, ; Seyitoglu et al., ; Cooper et al., ,b,c). However, prevalence studies in remote and urban areas have shown conclusively that a number of animal hosts, both domestic and native, have been exposed to C. burnetii , with these animals producing detectable antibodies (Cooper et al., ,b,c, ). The scope of risk associated with animal exposure other than large ruminants has to our knowledge not been widely examined in Australia.…”
Section: Introductionmentioning
confidence: 97%
“…The risk of contacting Q fever in a rural setting has been extensively reported, and the direct correlation between animal handlers contracting Q fever from large ruminants has been previously identified (Stoker and Marmion, ; Lang, ; Seyitoglu et al., ; Cooper et al., ,b,c). However, prevalence studies in remote and urban areas have shown conclusively that a number of animal hosts, both domestic and native, have been exposed to C. burnetii , with these animals producing detectable antibodies (Cooper et al., ,b,c, ). The scope of risk associated with animal exposure other than large ruminants has to our knowledge not been widely examined in Australia.…”
Section: Introductionmentioning
confidence: 97%
“…A cross‐sectional seroprevalence survey of Coxiella burnetii , the causative agent of Q fever, was performed in beef cattle in Queensland 5 . Seropositivity was 16.8%, which is in the upper ranges for the rest of the world.…”
Section: Production Animalsmentioning
confidence: 99%
“…This study was able to elucidate PCR evidence in wildlife urine and faecal samples as well as soil and dust samples. Another wildlife seroprevalence study performed by Cooper et al (2012) revealed 30.4% macropods were positive for C. burnetii by serology, followed by bandicoots (23.9%) and possums (10.7%) [9], [10], [11]. Furthermore C. burnetii has been isolated from ticks, particularly in the kangaroo-habituating Ambylomma triguttatum [12], [13].…”
Section: Introductionmentioning
confidence: 98%